Gender detection from frontal face images - Alam, Mirza Mohtashim; Rocky, Swagatam Roy (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.